A Comparison Between Omicron and Earlier COVID-19 Variants' Disease Severity in the Milan Area, Italy - Consolazio, David; Murtas, Rossella; Tunesi, Sara; Lamberti, Anna; Senatore, Sabrina; Faccini, Marino; Russo, Antonio Giampiero (Frontiers in Epidemiology, 2022)
Background In the context of the fourth wave of the COVID-19 pandemic in Italy, which occurred in correspondence with the outbreak of the Omicron variant, it became fundamental to assess differences in the risk of severe disease between Omicron and earlier SARS-CoV-2 variants that were still in circulation despite Omicron becoming prevalent. Methods We collected data on 2,267 genotyped PCR positive swab tests and assessed whether the presence of symptoms, the risk of hospitalization, and recovery times were significantly different between Omicron and earlier variants. Multivariable models adjusted for sex, age class, citizenship, comorbidities, and symptomatology allowed assessing the difference in the outcomes between Omicron and earlier variants according to vaccination status and its timing of administration. Results Compared to earlier variants in the same period, Omicron was less symptomatic, resulted in less hospital admissions for the unvaccinated and for those already immunized after the booster dose, and was associated with quicker recovery, though not for those with three vaccination doses. Conclusion Despite being milder, Omicron higher transmissibility and vaccine resistance should not let to underrate its damage potential, especially leading to hospitals and health services saturation.